Ooey gooey - Farber, Erica; Sansevere, John R. (New York : Random House, 1998)
When Captain Short Bob, the pirate king, cooks up a dish of bubble gum and tuna fish, he loses his gold tooth to a sea beast.
7 13 15
Keywords: Teeth -- Fiction; Stories in rhyme; Pirates -- Fiction